2022
DOI: 10.1371/journal.pone.0275314
|View full text |Cite
|
Sign up to set email alerts
|

A novel laboratory method to simulate climatic stress with successful application to experiments with medically relevant ticks

Abstract: Ticks are the most important vectors of zoonotic disease-causing pathogens in North America and Europe. Many tick species are expanding their geographic range. Although correlational evidence suggests that climate change is driving the range expansion of ticks, experimental evidence is necessary to develop a mechanistic understanding of ticks’ response to a range of climatic conditions. Previous experiments used simulated microclimates, but these protocols require hazardous salts or expensive laboratory equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The experimental conditions of the present study did not affect questing height, except for D. variabilis , which quested at significantly higher heights in warm, humid conditions. This is consistent with our previous study in which we observed that questing height was positively associated with RH in D. variabilis (Nielebeck et al, 2022). Since questing height affects the likelihood of contacting humans (Arsnoe et al, 2015), these results indicate that climate change may impact the risk of tick‐borne disease transmission differently depending on the behavioral and physiological ecology of the vector.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The experimental conditions of the present study did not affect questing height, except for D. variabilis , which quested at significantly higher heights in warm, humid conditions. This is consistent with our previous study in which we observed that questing height was positively associated with RH in D. variabilis (Nielebeck et al, 2022). Since questing height affects the likelihood of contacting humans (Arsnoe et al, 2015), these results indicate that climate change may impact the risk of tick‐borne disease transmission differently depending on the behavioral and physiological ecology of the vector.…”
Section: Discussionsupporting
confidence: 94%
“…A. americanum and I. scapularis ticks quested more frequently at the warmer experimental temperature. In a previous study, we observed that the proportion of D. variabilis ticks questing increased with drier conditions (Nielebeck et al, 2022). The experimental conditions of the present study did not affect questing height, except for D. variabilis , which quested at significantly higher heights in warm, humid conditions.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation